Economic Feasibility of Biomass Gasification for Electricity Generation in Pakistan (Global Journal of Science Frontier Research, 2015)
Due to increase in energy demands and depletion of conventional and fossil fuels in Pakistan, search has been started for alternative reliable and abundant available fuel, therefore demand of renewable sources has increased. Biomass is renewable and efficient source and very helpful for overcoming the current situation of energy crisis in Pakistan. It is promising fuel for future as it is effective enough to be applied on small and medium industrial scale. The major motivation of this research is to analyze the economic feasibility of a Biomass gasifier for the production of electricity. Biomass gasification is the most reliable and promising method now a days for generation of electricity because this process provides sustainable & affordable alternative to fossil fuel based process plants at small and medium levels. From economic analysis it is concluded that biomass gasification technology is the most feasible technology if it is implemented in rural areas with an average population of 200 houses and in small industries.
Keywords: biomass gasification; rice husk; waste wood; diesel; producer gas; economic analysis